2016
DOI: 10.5539/ijef.v8n2p94
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Capital Structure: Evidence from Selected Listed Companies in Sri Lanka

Abstract: This research examines the determinants of capital structure of selected listed companies in Sri Lanka. The capital structure of 55 companies listed in Colombo Stock Exchange (CSE) is empirically examined using the fixed effects model. Based on the findings of the panel data analysis during the period of 2003-2012, Profitability exhibits statistically significant of inverse relationship with leverage while firm size and growth shows statistically significant of positive relationship with leverage for selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
(35 reference statements)
6
21
0
1
Order By: Relevance
“…Pecking order theory also posits that with information asymmetry, higher growth opportunities in a firm means higher risks and hence such firm has the chance in raising debt. However, Smith and Watts (1992) and Pratheepan and Banda (2016) argue contrary that firms with higher growth opportunities will have low debt as capital.…”
Section: Pecking Ordermentioning
confidence: 98%
“…Pecking order theory also posits that with information asymmetry, higher growth opportunities in a firm means higher risks and hence such firm has the chance in raising debt. However, Smith and Watts (1992) and Pratheepan and Banda (2016) argue contrary that firms with higher growth opportunities will have low debt as capital.…”
Section: Pecking Ordermentioning
confidence: 98%
“…Gomez et al (2014) found the fact that profitability had a negative and significant effect on capital structure variable. This finding was further strengthened by Cortez & Susanto (2012), Ashraf & Rasool (2013) and Pratheepan & Yatiwella (2016)'s findings. However, Ross (1977), Frank & Goyal (2003), Baum et al (2007) and Wellalage & Locke (2015) found that there was a positive and significant effect between the two variables.…”
Section: Published By Sciedu Pressmentioning
confidence: 67%
“…Peneliti (Putra, 2012), (Arini, 2013), (Khairy, 2016), (Pratheepan, 2016), (Sahabuddin, 2017), (Astuti, 2018) Berdasarkan hasil pengujian diatas dengan menggunakan program spss 22, maka didapat persamaan regresi sebagai berikut : Y = a + β 1 X 1 -β 2 X 2 + β 3 X 3 + β 4 X 4 + β 5 X 5 + e Y= 0,529 + 0,765 -0,142 + 0,572 + 0,258 + 0,877 (0,393 > 0,05) maka ditarik kesimpulan bahwa kebijakan dividen tidak berpengaruh terhadap strukur modal. Hal ini karena perusahaan telah mencapai terhadap dewasa (mature), sehingga aliran kas perusahaan relatif lebih stabil dan cenderung menggunakan dana internalnya terlebih dahulu untuk membiayai investasinya sebelum menggunakan pembiayaan eksternal melalui hutang.…”
Section: Pengaruh Company Growth Terhadap Struktur Modalunclassified